PELATIHAN LITERASI KEUANGAN DALAM PENGELOLAAN KEUANGAN UMKM KLINIK WONOSARI AEK KANOPAN YANG SISTEMATIS - Raja Saul Marto Hendry (JURNAL BIMA, 2026)
This community service program was implemented at Klinik Wonosari Aek Kanopan, a micro-enterprise in Aek Kanopan Village, Kualuh Hulu  District, North Labuhanbatu Regency, which faced a major issue of limited financial literacy of a systematic recording system. Thus, this community service activity aims to increase the knowledge of business actors in managing business finances, in order to obtain optimal business financial performance.The activities consisted of preliminary surveys, training, mentoring, and evaluation, focusing on the separation of personal and business finances, transaction recording, Cost of Goods Sold (COGS) calculation, and simple profit–loss analysis. The results indicated a significant improvement in the business owner’s understanding, with a 38% increase in the post-test score compared to the pre-test. Furthermore, the business began implementing real-time financial records, evaluating sales targets, and determining prices based on factual data. These findings highlight the importance of financial literacy in supporting the sustainability of micro-enterprises and their contribution to family welfare and the local economy.